2007
DOI: 10.1038/sj.npp.1301558
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of CB1 Receptor in the Rat Striatum: Localization and Effects on D1 and D2 Dopamine Receptor-Mediated Motor Behaviors

Abstract: Cannabinoid CB 1 receptors are densely expressed on striatal projection neurons expressing dopamine D 1 or D 2 receptors. However, the specific neuronal distribution of CB 1 receptors within the striatum is not known. Previous research has established that the endocannabinoid system controls facilitation of behavior by dopamine D 2 receptors, but it is not clear if endocannabinoids also modulate D 1 receptor-mediated motor behavior. In the present study, we show that cannabinoid CB 1 receptor mRNA is present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 61 publications
9
99
0
2
Order By: Relevance
“…This statement is based in the subsequent evidence: First, it has been described the presence of the CB 1 cannabinoid receptor in wake-related brain areas including hypothalamus and pons (Miederer et al, 2013;Soni et al, 2014). Second, there is an interactive relationship between the CB 1 cannabinoid receptor and DA system (Degroot et al, 2006;Davis and Nomikos, 2008;Martin et al, 2008;Kleijn et al, 2012;Dazzi et al, 2014). Third, previous reports have shown that SR141716A enhances NE contents (Tzavara et al, 2001(Tzavara et al, , 2003Bedse et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This statement is based in the subsequent evidence: First, it has been described the presence of the CB 1 cannabinoid receptor in wake-related brain areas including hypothalamus and pons (Miederer et al, 2013;Soni et al, 2014). Second, there is an interactive relationship between the CB 1 cannabinoid receptor and DA system (Degroot et al, 2006;Davis and Nomikos, 2008;Martin et al, 2008;Kleijn et al, 2012;Dazzi et al, 2014). Third, previous reports have shown that SR141716A enhances NE contents (Tzavara et al, 2001(Tzavara et al, , 2003Bedse et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…CB 1 receptors are also densely located on presynaptic terminals of GABAergic MSNs projecting to SNpr [13]. CB 1 receptors have been detected both in direct striatonigral and D1-expressing neurons and in striatopallidal and D2-expressing neurons [12]. Also other efferent striatal outputs such as GP in humans, the entopeduncular nucleus in rodents, and the GABAergic projections from the GP to the STN contain high level of CB 1 receptors [13].…”
Section: Pd Cb 1 Distribution and Ecb-dependent Plasticitymentioning
confidence: 97%
“…mRNA expression of CB 1 receptors are maximally present at BG level [12]. The localization of CB 1 receptors on presynaptic axon terminals of glutamatergic corticostriatal projecting neurons represents a key factor in the fundamental contribution of the eCB system to different forms of striatal plasticity.…”
Section: Pd Cb 1 Distribution and Ecb-dependent Plasticitymentioning
confidence: 99%
“…Cannabinoid type 1 receptors (CB1Rs) are expressed in the basal ganglia where they regulate intracellular levels of cAMP by interacting with Gi/o and Gs proteins in the direct and indirect pathways, respectively (Glass, Dragunow, & Faull, 1997;Herkenham et al, 1991;Mailleux & Vanderhaeghen, 1992;Martín et al, 2008). A PET study using [ 18 F]MK-9470 has shown significant decreases in CB1R levels in the substantia nigra of early de novo and advanced PD patients with and without LIDs (van Laere et al, 2012).…”
Section: Cannabinoidmentioning
confidence: 99%